Management, 11th Edition - Schermerhorn, John (John Wiley & Sons, 2010)
Completely updated and revised, this eleventh edition arms managers with the business tools they'll need to succeed. The text presents managerial concepts and theory related to the fundamentals of planning, leading, organising, and controlling with a strong emphasis on application. It offers new information on the changing nature of communication through technology. Focus is also placed on ethics to reflect the importance of this topic, especially with the current economic situation. This includes all new ethics boxes throughout the chapters. An updated discussion on the numerous legal law changes over the last few years is included as well. Managers will be able to think critically and make sound decisions using this text because the concepts are backed by many applications, exercises, and cases.